'Look, wait, I'll translate': Refugee Women's Experiences with Interpreters in Healthcare in Aotearoa New Zealand - Cassim, S; Kidd, J; Ali, M; Abdul Hamid, N; Jamil, D; Keenan, R; Begum, F; Lawrenson, R (CSIRO, 2022)
This study aimed to explore refugee women's experiences of interpreters in healthcare in Aotearoa, New Zealand (NZ). Semi-structured interviews were conducted with nine women who arrived in NZ as refugees. Analysis involved a 'text in context' approach. An iterative and interpretive process was employed by engaging with participant accounts and field notes. The various meanings behind participants' experiences were unpacked in relation to the literature and the broader socio-cultural contexts in which these experiences occurred. Findings highlighted issues with professional and informal interpreters. These issues included cost, discrepancies in dialect, translation outside appointments, and privacy. Findings indicate ethical and practical implications of using interpreters in healthcare for refugee women. A step to achieving equitable healthcare for refugee women in New Zealand entails putting in place accessible and robust communicative infrastructure.
Keywords: Access; Barrier; Ethics; Interpreter; Language barrier; Refugee; Translator; Women